Efektivitas Hukum Jaminan Performa Kredit UMKM Melalui Penerapan Innovative Credit Scoring - Shannia Angelia Rahardjo; Tarsisius Murwadji; Helza Nova Lita (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a significant role in the economy, but often face obstacles in accessing financing. Credit performance guarantee is one of the mechanisms to mitigate risks for financial institutions. Along with the development of financial technology, innovative credit scoring emerged as an alternative method of assessing the creditworthiness of MSMEs. This research aims to analyze the legal effectiveness of the application of MSME credit performance guarantees based on innovative credit scoring. This research uses a normative juridical method with qualitative juridical analysis to try to examine and analyze the problems studied. The application of innovative credit scoring in MSME credit performance guarantees has the potential to increase the legal effectiveness of guarantees through a more comprehensive and accurate risk assessment. However, its implementation requires regulatory clarity regarding scoring standards, personal data protection, and dispute resolution mechanisms. An adaptive and responsive legal framework to technological innovation is crucial to optimize the role of innovative credit scoring in strengthening the effectiveness of MSME credit performance guarantees and promoting financial inclusion.